Nilai-Nilai Humanis Dalam Komunitas Segawon (Seduluran Nek Gadah Perlu Mawon) Di Kabupaten Wonosobo - Ahmad Fatih; Deni Sutan Bahtiar; Robingun Suyud El Syam (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Happy is the need of every human being, so it is necessary to refresh so that humans can express their feelings, not be trapped in a rigid atmosphere so that values ​​as humans who have the right to be happy and appreciated can be realized. Through a field approach, the research results: that there are humanist values ​​in the Segawon community, namely brotherhood, kinship, solidarity, virtue, intimacy, dialogue, tolerance and tolerance. These values ​​support a harmonious atmosphere so that community members can be successful in life.